The Minimum Legal Drinking Age and Crime - Carpenter, Christopher; Dobkin, Carlos (The Review of Economics and Statistics, 2015)
We use variation from the minimum legal drinking age to estimate the causal effect of access to alcohol on crime. Using a census of arrests in California and a regression discontinuity design, we find that individuals just over age 21 are 5.9% more likely to be arrested than individuals just under 21. This increase is mostly due to assaults, alcohol-related offenses, and nuisance crimes. These results suggest that policies that restrict access to alcohol have the potential to substantially reduce crime.